Klasifikasi Ilmu Menurut Ibn Sina - Nur Khasanah; Achmad Irwan Hamzani; Havis Aravik (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2020)
AbstractThis thesis addresses the classification of knowledge by Ibn Sina. The goal of this thesis was to decide the classification of knowledge according to Ibn Sina and to what degree the position and effect of Ibn Sina's thinking on the growth of science in Islam. This research is a qualitative literature-based study (library research). The method used is analytical, qualitative, with the goal of presenting a definition or explaining the present reality or what is happening or the current reality of the object under study. The results of this study show that the classification of knowledge according to Ibn Sina divides knowledge into two, namely theoretical knowledge (hikmah nadzariah) which seeks to purify the soul through ma'rifat. What this information requires is the discussion of the questions of metaphysics (divinity), mathematics (riyadhiyah) and physics (thabi'iyah). Second, the functional sciences ('Amaliah'). Included in the area of practical science, such as ethics (Khuluqiyah), regulating family relationships in the household, economics (Tadbir al-Manzil), regulating the association of people within the state (Tadbir al-Madinah) and prophethood (syari'ah).Keywords; Ibn Sina, Classification of Science, theoretical science, practical science. AbstrakStudi ini membahas tentang klasifikasi ilmu menurut Ibn Sina. Dengan tujuan untuk mengetahui klasifikasi ilmu menurut Ibn Sina dan sejauh mana peran dan pengaruh pemikiran Ibn Sina terhadap perkembangan ilmu pengetahuan dalam Islam. Studi merupakan studi kualitatif berbasis kepustakaan (library research). Pendekatan yang digunakan adalah deskriptif kualitatif yang bertujuan untuk memberi gambaran atau mendeskripsikan kenyataan yang ada atau apa yang terjadi atau kenyataan sebenarnya pada obyek yang diteliti. Hasil penelitian ini memperlihatkan bahwa klasifikasi ilmu menurut Ibn Sina ilmu terbagi menjadi dua, yaitu ilmu teoritis (hikmah nadzariyah) bertujuan untuk membersihkan jiwa melalui ma’rifat. Yang termasuk ilmu ini adalah membahas masalah-masalah metafisika (ketuhanan), matematika (riyadhiyah), dan fisika (thabi’iyah). Kedua, ilmu-ilmu praktis (‘Amaliyah). Termasuk dalam bidang ilmu-ilmu praktis seperti etika (Khuluqiyah), mengatur pergaulan keluarga dalam rumah tangga, ekonomi (Tadbir al-Manzil), mengatur pergaulan umat dalam negara (Tadbir al-Madinah) dan kenabian (syari’ah).Kata Kunci; Ibn Sina, Klasifikasi Ilmu, Ilmu teoritis, ilmu praktis.